From research to a political commitment to strengthen access to surgical, obstetric, and anesthesia care in Africa by 2030 - M'pele, Pierre; Seyi-Olajide, Justina O.; Elongo, Tarcisse; Lemvik, Jorn; Dovlo, Delanyo; Ameh, Emmanuel A. (Frontiers in Public Health, 2023)
Objective This study aimed to engage African leaders and key stakeholders to commit themselves toward the strengthening of surgical, obstetric, and anesthesia care systems by 2030 in Africa. Methods From research to a political commitment, a baseline assessment was performed to foster the identification of the gaps in surgical care as a first step of an inclusive process. The preliminary findings were discussed during the International Symposium on Surgical, Obstetric, and Anesthesia Systems Strengthening by 2030 in Africa. The conclusions served to draft the Dakar Declaration and its Regional Action Plan 2022–2030 to improve access to surgical care by 2030 in Africa, endorsed by Heads of State. Results The International Symposium was composed of two meetings that gathered (i) 85 scientific experts and (ii) 28 ministers of health or representatives from 28 sub-Saharan African countries. The 28 African countries represent (i) 51% of the continent's total population, (ii) 68% of the 47 African countries of the WHO Africa Region, (iii) 58% of all African Union countries, and (vi) 79% (3,371) of the WHO Africa Region's total (4,271) health districts. The International Symposium and the Heads of State Summit successfully produced the Dakar Declaration on access to equitable, affordable, and quality Surgical, Obstetric, and Anesthesia Care by 2030 in Africa and its Regional Actions Plan 2022–2030 which prioritizes 12 urgent actions needed to be implemented, six strategic priorities, 16 key indicators, and an annual dashboard to monitor progress. Conclusion The Dakar Declaration and its Regional Action Plan 2022–2030 are a commitment to establish quality and sustainable surgical, obstetric, and anesthesia care in each African country within the ambitious framework of “The Africa we want” Agenda 2063.